(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The aim of this study was to measure the concentration of some heavy metals (Iron, copper, zinc, chromium, manganese, cobalt, lead, nickel) in five types of cigarettes (Marlboro, Rothmans, LM, Sports, Karela) in some of aden govemorate markets_ Sebha, at arate of three samples of each type, the Atomic Absorption Spectrophotometer technique was used to determine heavy metals. The results showed a significant increase in the concentration of heavy metals in types of cigarettes at probability of (P<0.01). The concentration of the heavy metals was (0.049, 0.037, 0.027, 0.04, 0.019, 0.083, 0.077 µg/g) respectively. while the results of the survey showed the highest percentage of smokers in the age group 45 ((28.9%) and the lowest in the 5-14 (0.02%) and children 5-14 (2%), and the highest percentage of smokers. Smoking years 1-9 years amounted to (47.7%), the number of cigarettes smoked per day was 9-10 cigarettes (47%), while the percentage of smokers for university education (55%), intermediate education (34.9%), illiterate (10.%). And the health implications recorded that the most common diseases in the studied sample were shortness of breath (10.1%), cough (6.3%), gingivitis (2%) and pneumonia (1.3%).